X-ray peak broadening on microstructure, and structural properties of titanium and Ti-6Al-4V alloys. (2020) - Ali, Showkat; Karunanithi, R.; Prashanth, M.; Rahman, M. Abdur
Abstract: In this present work, the effect of milling duration on the microstructure and structural properties of titanium and Ti-6Al-4V alloy powders were investigated. Ti and Ti-6Al-4V alloy powders were mechanically alloyed using high energy planetary ball mill for different milling durations (AR, 10 and 20 h) at room temperature. The milled powders were characterized by XRD and HR-SEM analysis. Structural properties such as Crystal size, lattice strain, dislocation density and lattice parameter were examined by using X-ray peak broadening analysis in Williamson hall method i.e., Uniform Deformation Model (UDM). XRD peaks for different milled powders showed significant peak broadening and grain refinement. The Microstructure and size distribution of powder particles, grain size and morphology of Ti and Ti-6Al-4V alloy milled powders were characterized using High Resolution Scanning Electron Microscope (HR-SEM).